Efeito da espécie invasora Hedychium coronarium J. König (Zingiberaceae) na evapotranspiração e no lençol freático - Vergne, Driélli de Carvalho (2020)
Biological invasions are among the main causes of biodiversity loss, to being able to change processes at ecosystems’ level, such as primary and secondary productivity, nutrient cycling, hydrological cycle, soil development and disturbance frequency. Changes caused by invasive species in the composition of environment can reduce or eliminate the provision of ecosystem services. Water is one of those services that can be damage by biological invasion, and evapotranspiration (ET) and variation in the water table level can also be affected. We assessed the impact of the Hedychium coronarium species on ET over 14 months and water table level, in an invaded and non-invaded area. We calculated the reference evapotranspiration (ET0) and hence the plant coefficient (Kp) for the invasive species and a group of native species of riparian forest; and we relate the growth of species to the monthly ET. The daily ET exhibited by H. coronarium was low compared to native species and mixture of invasive and native species. Thus, daily ET and accumulated ET of the mixture was higher than the other treatments, showing that the heterogeneity of the vegetation presents higher ET values. In addition, monthly ET was related to height, diameter at ground level and number of genets (for H. coronarium) indicating that species (invasive or native) have greater investment in growth to find light and occupy the area. The Kp values tend to increase over time reflecting the different stages of development of these species. Water table depth was greater in the invaded areas. Our results show that anthropic actions are directly linked to the invasion processes by H. coronarium and that the absence of natural enemies, as well as the competitive ability of this species, favors the environments’ dominance, which reduces evapotranspiration, as well as infiltration of water in the soil. In addition, this species is can cause positive feedback for its own advantage.